2018
DOI: 10.1002/ajmg.a.38724
|View full text |Cite
|
Sign up to set email alerts
|

KBG syndrome patient due to 16q24.3 microdeletion presenting with a paratesticular rhabdoid tumor: Coincidence or cancer predisposition?

Abstract: KBG syndrome is a rare autosomal dominant disorder caused by constitutive haploinsufficiency of the ankyrin repeat domain-containing protein 11 (ANKRD11) being the result of either loss-of-function gene variants or 16q24.3 microdeletions. The syndrome is characterized by a variable clinical phenotype comprising a distinct facial gestalt and variable neurological involvement. ANKRD11 is frequently affected by loss of heterozygosity in cancer. It influences the ligand-dependent transcriptional activation of nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
0
11
1
Order By: Relevance
“…Seven patients (patients 7, 8, 9, 13, 20, 26, 38 in Supplementary Material, Table S1 ) out of the 44 evaluable individuals (15,6%), did not display ID. Severe ID was identified only in two patients with concomitant genetic conditions ( 12 , 16 ), namely maternal 15q11.2 deletion and paternal inherited exostosis due to EXT1 mutation , respectively. About 18% of patients presented hypotonia at birth or at the first evaluation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven patients (patients 7, 8, 9, 13, 20, 26, 38 in Supplementary Material, Table S1 ) out of the 44 evaluable individuals (15,6%), did not display ID. Severe ID was identified only in two patients with concomitant genetic conditions ( 12 , 16 ), namely maternal 15q11.2 deletion and paternal inherited exostosis due to EXT1 mutation , respectively. About 18% of patients presented hypotonia at birth or at the first evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…Epilepsy was present in 26.5% of patients (13/49) and mostly correlated with cerebral anomalies at the MRI. Indeed, out of 13 patients who developed seizures, eight presented brain anomalies, in three of them ( 12 , 25 , 26 ) no cerebral alteration was detected by brain imaging and in two of them no MRI was performed. Electroencephalography (EEG) often revealed mild non-specific background abnormalities with modest voltage asymmetry, slow background activity (patient 2, 8, 47) or an irregular brain activity during sleeping (patient 41).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ANKRD11 expression was shown to be downregulated in breast cancer cell lines. Moreover, Behnert et al (29) reported a 17-year-old patient who was diagnosed with a left-sided paratesticular extrarenal malignant rhabdoid tumor. Genetic testing identified a constitutional de novo 16q24.3 microdeletion leading to the loss of the entire ANKRD11 locus.…”
Section: Discussionmentioning
confidence: 99%
“…Noriko Fuke, 1 Sae Nishisho, 1 Aya Tanaka, 2 Ryuichi Shimono 2 and Takashi Kusaka 1 Department of 1 Pediatrics, 2 Pediatric Surgery, Faculty of Medicine, Kagawa University, Kagawa, Japan Key words ascites, pharmacotherapy resistance, pleuroperitoneal communication, quality of life.…”
Section: Fundingmentioning
confidence: 99%